Unraveling correlativities: social network analysis in engineering curricula - Tarifa, Héctor Ramón (AWARI, 2024)
As an institution of higher learning, the university bears the responsibility of producing graduates who are highly trained and possess the capacity to adapt to change. To achieve this level of academic quality, it is essential to implement evaluation mechanisms, establish control practices, facilitate professionalization practices, and, most importantly, ensure that the curriculum is regularly updated in terms of content and competencies to provide the training of future graduates is aligned with current and future professional standards. In particular, the curriculum, which establishes the graduate profile, requirements, minimum contents, correlativity system, and subjects that organize the knowledge, skills, and competencies that students must acquire, is embodied in the curricular design. To ensure the quality of the academic offer, it is essential to assess the alignment between the curriculum, the teaching-learning process, and the attainment of the graduate profile, establishing this as the foundation for a continuous improvement cycle in the curricular offer. This article presents a relational model derived from the correlativity system of an undergraduate curriculum of a university degree program. The model was developed by applying social network analysis concepts, methods, and tools, which allowed for the characterization of the system and the identification of its most relevant components and interactions.